An Action Research on Enhancing Grade 10 Student Creative Thinking Skills using Argument-driven Inquiry Model in the Topic of Chemical Environment - Pitukpong Kumdang; Sirinapa Kijkuakul; Wipharat Chuachuad Chaiyasith (Journal of Science Learning, 2018)
A goal of the 21st-century education is to enhance students’ creative thinking skills as the basis for construction of innovations for developing countries. Generally, previous teaching tradition, teacher-centered approach, are used in many classrooms, however, failed the goal. Therefore, this study aims to promote Grade 10 Thai students’ creative thinking by implementing Argument-Driven Inquiry (ADI) through three cycles of action research. There are 31 students participated in the study. The student data are collected using learning journals, artifacts and informal interviews then analyzed with content analysis and method triangulation. The findings indicate that students have a progression in creative thinking. They can develop skills of curiosity, originality, fluency, imagination, elaboration, and flexibility respectively. As a recommendation, it is necessary that teaching for that success needs integrations among chemical environment, geography, and art.